Skullcapflavone I protects cardiomyocytes from hypoxia-caused injury through up-regulation of lincRNA-ROR. (June 2019) - Zhang, Zhenxiao; Li, Hui; Liu, Mingyang; He, Jianshuai; Zhang, Xiaotian; Chen, Yuehua
Myocardial infarction (MI) is a serious heart disease in which cardiomyocytes are damaged, caused by hypoxia. This study explored the possible protective activity of Skullcapflavone I (SF I), a flavonoid isolated from the root of Scutellaria baicalensis Georgi, on hypoxia-stimulated cardiomyocytes cell injury in vitro . Viability and apoptosis of H9c2 cells and primary cardiomyocytes were tested using cell counting kit–8 (CCK-8) assay and Guava Nexin Reagent, respectively. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) was used to measure the long non-coding RNA regulator of reprogramming (lincRNA-ROR) expression. si-ROR was transfected to knockdown lincRNA-ROR. Western blotting was conducted to assess the protein levels of key molecules related to cell proliferation, apoptosis, and mitogen-activated protein kinase/extracellular signal–regulated kinase (MEK/ERK) pathway. We discovered that hypoxia stimulation obviously reduced H9c2 cell and primary cardiomyocytes' viability and proliferation, but promoted cell apoptosis. SF I treatment mitigated the cell viability and proliferation inhibition, as well as cell apoptosis caused by hypoxia. Moreover, SF I promoted the hypoxia-caused up-regulation of lincRNA-ROR in H9c2 cells and primary cardiomyocytes. Knockdown of lincRNA-ROR reversed the influence of SF I on hypoxia-stimulated H9c2 cells and primary cardiomyocytes. Besides, SF I activated MEK/ERK pathway in H9c2 cells and primary cardiomyocytes via up-regulating lincRNA-ROR. To sum up, our research verified the beneficial activity of SF I on hypoxia-caused cardiomyocytes injury. SF I protected cardiomyocytes from hypoxia-caused injury through up-regulation of lincRNA-ROR and activation of MEK/ERK pathway.